High-fructose diet downregulates long-chain acyl-CoA synthetase 3 expression in liver of hamsters via impairing LXR/RXR signaling pathway - Dong, Bin (The American Society for Biochemistry and Molecular Biology, 2013)
Long-chain acyl-CoA synthetases (ACSL) play key roles in fatty acid metabolism in liver and other metabolic tissues in an isozyme-specific manner. In this study, we examined the effects of a fructose-enriched diet on expressions of ACSL isoforms in the liver of hamsters. We showed that the fructose diet markedly reduced the mRNA and protein expressions of ACSL3 in hamster liver without significant effects on other ACSLs. The decrease in ACSL3 abundance was accompanied by a reduction in ACSL-catalyzed synthesis of arachidonyl-CoA and oleoyl-CoA in liver homogenates of hamsters fed the fructose diet as opposed to normal diet. We further showed that fructose diet specifically reduced expressions of three key components of the LXR signaling pathway, namely, liver X receptor (LXR)α, LXRβ, and retinoid X receptor (RXR)β. Exogenous expression and activation of LXRα/β increased hamster ACSL3 promoter activities in a LXR-responsive element (LXRE)-dependent fashion. Finally, we showed that treating hamsters with LXR agonist GW3965 increased hepatic ACSL3 expression without affecting other ACSL isoforms. Furthermore, the ligand-induced increases of ACSL3 expression were accompanied with the reduction of hepatic triglyceride levels in GW3965-treated hamster liver. Altogether, our studies demonstrate that fructose diet has a negative impact on LXR signaling pathway in liver tissue and reduction of ACSL3 expression/activity could be a causal factor for fructose-induced hepatic steatosis.